Today’s choice of antiepileptic therapy: stages and recommendations - K. V. Voronkova; A. E. Nikitin; I. G. Rudakova; P. N. Vlasov; S. G. Burd; A. V. Lebedeva; G. N. Avakyan (Эпилепсия и пароксизмальные состояния, 2018)
At present, treatment recommendations are developed considering the principles of evidence-based medicine. General practitioners (GP) are offered a choice of different medications with the known  characteristics of efficacy and tolerance. For a GP, the right choice of the optimal drug from the  proposed list may become a problem. Therefore, it is important not only to provide complete  information on all treatment options for a patient with epilepsy, but also discuss a scheme of the  proposed therapy (“key”) so to guide a GP through the treatment options and assess the possibility of  alternative treatment strategies. Contrary to the trial and error method, when the drug efficacy and  safety is assessed during the treatment, the proposed optimized approach allows for achieving a maximal therapeutic effect in patients with epilepsy.